An adaptive model predictive control strategy for a class of discrete‐time linear systems with parametric uncertainty. (4th October 2021) - Hu, Yingjie; Gou, Linfeng; Fan, Ding; Iu, Herbert Ho‐Ching; Fernando, Tyrone; Zhang, Xinan
Summary: In this study, an adaptive model predictive control (MPC) strategy is proposed for a class of discrete‐time linear systems with parametric uncertainty. In the presented adaptive MPC, an updating law is firstly designed to update the estimated parameters online. By utilizing the estimated parameters, a standard MPC optimization problem for unconstrained systems is established. Then, to deal with constrained systems, the min–max MPC technique is developed under the set‐based approach for the estimated parameters. Furthermore, it is shown theoretically that the recursive feasibility and closed‐loop stability can be rigorously proved, respectively. Finally, numerical simulations and comparative analysis are presented to illustrate the superiority of the proposed algorithms in control performance.